The Challenge of Training Professional Profiles Online Media Based on Innovation and Knowledge Technologies - Flores, Jesús Miguel; Salinas Aguilar, Cecilia (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2012)
The natural evolution of the blogs, social networks and other digital resources used in thecontext of the media, demands a professional profile type increasingly specific. The mass media, toglobal scale, trying to adapt or face the media revolution that has caused by Internet. Are media who have risked their investments what has become bearers of that revolution. So, as a result of this adaptation of media organizations to the call convergence, emerging new professional profiles, asemerged in recent years of the nineties. Different job profiles are described and analyzed by experts and scholars in the evolution of journalism, which show the media are adapting to new environments, because ift hey do not run the risk of simply disappearing from the media space. In this article proposes a more detailed and current information about professional profiles online media demanding, from a stand point of training in schools, and their presence, expansion and consolidation in the most advanced media.